2018
DOI: 10.1002/marc.201800260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Trifluoromethylated Quinoxaline‐Based Polymers for Photovoltaic Applications

Abstract: A series of quinoxaline-based conjugated polymers, in which the electron-donating benzodithiophene (BDT) unit is linked to the electron-accepting 6,7-difluorinated quinoxaline (DFQ) derivatives by a thiophene bridge, is synthesized. To investigate their effects on the intrinsic properties of polymers, strong electron-withdrawing trifluoromethyl (CF ) groups were incorporated into the meta-position of the phenyl ring at the 2,3-positions of the DFQ unit of the reference polymer, labelled PEhB-FQx, to yield the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Interestingly, after further introducing the "F" atom into the Qx unit, Chen et al reported a novel polymer donor PBDT-TFQ (2012) ; [202] Putri and co-workers preparedPEhB-FQx (2018) and PEhB-FQxCF3 (2018) . [203] After applying for OSC devices, PBDT-TFQ: PC 71 BM based, PEhB-FQx: PC 71 BM based and PEhB-FQxCF3: PC 71 BM based OSCs obtained theV oc of 0.76, 0.68 and 0.88 V;J sc of 17.9, 11.1 and 12.2 mA/cm 2 , FF of 57.6, 63.5 and 57.8%; andPCE of 7.8, 4.68 and 7.26%, respectively. Compared with the P(BDT-DTQx): PC 71 BM based OSC, Qx unit with a strong electronegative significantly decreases the HOMO energy level of P(BDT-DTQx) and accelerates the hole/electron mobility in the active layer, thereby P(BDT-DTQx): PC 71 BM based OSC obtains a higher V oc and J sc .…”
Section: As For the Main-chain Engineering Bdt-t-bsdz-t Bdt-t-btz-t A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, after further introducing the "F" atom into the Qx unit, Chen et al reported a novel polymer donor PBDT-TFQ (2012) ; [202] Putri and co-workers preparedPEhB-FQx (2018) and PEhB-FQxCF3 (2018) . [203] After applying for OSC devices, PBDT-TFQ: PC 71 BM based, PEhB-FQx: PC 71 BM based and PEhB-FQxCF3: PC 71 BM based OSCs obtained theV oc of 0.76, 0.68 and 0.88 V;J sc of 17.9, 11.1 and 12.2 mA/cm 2 , FF of 57.6, 63.5 and 57.8%; andPCE of 7.8, 4.68 and 7.26%, respectively. Compared with the P(BDT-DTQx): PC 71 BM based OSC, Qx unit with a strong electronegative significantly decreases the HOMO energy level of P(BDT-DTQx) and accelerates the hole/electron mobility in the active layer, thereby P(BDT-DTQx): PC 71 BM based OSC obtains a higher V oc and J sc .…”
Section: As For the Main-chain Engineering Bdt-t-bsdz-t Bdt-t-btz-t A...mentioning
confidence: 99%
“…In addition, to further exploring the effect of fluorinated Qx unit in polymer skeleton BDT-T-Qx-T, Bolognesi et al first reportedP(2) (2013) in 2013; [205] PFQBDT-TR1 (2014) and PFQBDT-TR2 (2014) were synthesized by Tessarolo et al; [207] PBQ-3 (2015) and PBQ-4 (2015) were designed by Liu et al; [206] PBDTTFTQ-EH (2015) ,PBDTTFTQ-DO (2015) , PBDTTFTTQ-EH (2015) andPBDTTFTTQ-DO (2015) with different types of thiophene-based and benzene-based side chains were reported by Wu et al; [208] Wang and co-workers fabricatedPBDT-DFQX-TP (2015) and PBDT-DFQX-TT (2015) . [209] Moreover, a series of novel polymer donors PffQx-T (2016) ; [210] HFQx-BDT (2017) ; [211] OFQx-T (2017) and EOFQx-T (2017) ; [212] PBDT-DFQX-TTSEH (2017) and PBDT-DFQX-TTSCS (2017) ; [213] PThB-FQxCF3 (2018) ; [203] WF3 (2019) , WF3S (2019) and WF3F (2019) ; [214] TTFQx-T1 (2019) ; [215] PBQ10 (2020) ; [216] PBQ5 (2021) andPBQ6 (2021) [217] were also successfully synthesized. Among these donors, under the synergistic optimization by introducing "F" atoms and side chains with a suitable π-π conjugated, the V oc in these polymer donor: acceptor based OSCs stay at a high level, especially for P(2): PC 61 BM based (0.90 V), PFQBDT-TR2: PC 61 BM based (0.96 V), PBQ-4: PC 71 BM based (0.90 V), HFQx-BDT: ITIC based (0.92 V) and EHFQx-T: PC 71 BM based (0.91 V) OSCs.…”
Section: As For the Main-chain Engineering Bdt-t-bsdz-t Bdt-t-btz-t A...mentioning
confidence: 99%
“…In particular, CF 3 moieties were loaded on the meta-position of benzenes at the 2,3-position quinoxaline acceptor to enhance the photovoltaic nature of all polymers. 26 After preparing the reference polymer PBF-CF 3 Qx, additional electron-withdrawing F atoms and electron-donating methoxy (OCH 3 ) units were selectively introduced at the 6,7-positions of the quinoxaline unit of the PBF-CF 3 Qx reference for generating two objective polymers, PBF-CF 3 QxF and PBF-CF 3 QxM, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Electron-donating benzodithiophene (BDT) and electron-accepting quinoxaline monomers decorated with strong electron-withdrawing F atoms and trifluoromethyl (CF 3 ) units, respectively, were used as the basic D and A constituents, respectively, along the chain. In particular, CF 3 moieties were loaded on the meta -position of benzenes at the 2,3-position quinoxaline acceptor to enhance the photovoltaic nature of all polymers . After preparing the reference polymer PBF-CF 3 Qx, additional electron-withdrawing F atoms and electron-donating methoxy (OCH 3 ) units were selectively introduced at the 6,7-positions of the quinoxaline unit of the PBF-CF 3 Qx reference for generating two objective polymers, PBF-CF 3 QxF and PBF-CF 3 QxM, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The low-lying HOMO energy level of polymeric donors can enhance the open-circuit voltage ( V oc ) of the device, which can also trigger a sharp increase in PCE. Along with fluorine atoms, other electron-withdrawing units, such as trifluoromethyl (–CF 3 ), sulfonyl (–SO 2 ), and cyano (–CN) groups, were utilized during the preparation of D–A type conjugated polymers [28,29,30]. In particular, the incorporation of the CN group into the chemical structures of D–A type polymers is beneficial for achieving high-performance PSCs, because the CN unit can not only facilitate the charge separation process in BHJ device through the generation of strong dipole moment, but also stabilize the LUMO and HOMO energy levels of polymers [30,31].…”
Section: Introductionmentioning
confidence: 99%